Cross-Cultural Adaptation, Reliability, and Validity of a Turkish Version of the Work Rehabilitation Questionnaire (WORQ-Turkish) - Aran, Orkun Tahir; Abaoğlu, Hatice; Çağlar, Gamze Ekici; AKEL, BURCU SEMİN; Aki, Esra; Karahan, Sevilay; Kayıhan, Hülya (Springer Plenum, 2021)
PurposeThe Work Rehabilitation Questionnaire (WORQ) is an instrument based on the International Classification of Functioning Vocational rehabilitation core set. The aim of this study was to analyze the validity, reliability and cross-cultural adaptation of the WORQ to Turkish and evaluate its psychometric properties.MethodsThe cross-cultural adaptation and translation procedures were conducted following Beaton's guidelines. The test-re-test reliability was examined by Spearman Brown Coefficient (split half analysis), internal consistency was examined by Cronbach's alpha. Criterion related validity of the WORQ was determined by Beck Depression Inventory using Pearson correlation coefficient and known group differences regarding age, gender, work and educational levels using one-way ANOVA and t test. Construct validity was examined by confirmatory factor analysis using AMOS.ResultsTwo hundred and fifty-seven participants with disabilities were included to the study from seven different provinces of Turkey. The WORQ-Turkish showed excellent internal consistency (0.906), good test-retest reliability (0.811), and good construct validity (good model fit indices). Criterion related validity analysis showed medium correlations between WORQ and Beck Depression Inventory (p < 0.001), however there were no statistical significant differences regarding known group parameters (p > 0.05).ConclusionsIn this study, the cross-cultural adaptation, and validity and reliability of WORQ-Turkish self-reported version were examined and the results indicated that WORQ-Turkish was a valid and reliable scale for analyzing vocational rehabilitation process of people with disabilities.
Keywords: Validation Studies; People With Disabilities; Work; Psychometrics